Components of the Secondary Pathway Stimulate the Primary Pathway of Eukaryotic Okazaki Fragment Processing - Henry, Ryan A. (American Society for Biochemistry and Molecular Biology, 2010)
Reconstitution of eukaryotic Okazaki fragment processing implicates both one- and two-nuclease pathways for processing flap intermediates. In most cases, FEN1 (flap endonuclease 1) is able to efficiently cleave short flaps as they form. However, flaps escaping cleavage bind replication protein A (RPA) inhibiting FEN1. The flaps must then be cleaved by Dna2 nuclease/helicase before FEN1 can act. Pif1 helicase aids creation of long flaps. The pathways were considered connected only in that the products of Dna2 cleavage are substrates for FEN1. However, results presented here show that Dna2, Pif1, and RPA, the unique proteins of the two-nuclease pathway from Saccharomyces cerevisiae, all stimulate FEN1 acting in the one-nuclease pathway. Stimulation is observed on RNA flaps representing the initial displacement and on short DNA flaps, subsequently displaced. Neither the RNA nor the short DNA flaps can bind the two-nuclease pathway proteins. Instead, direct interactions between FEN1 and the two-nuclease pathway proteins have been detected. These results suggest that the proteins are either part of a complex or interact successively with FEN1 because the level of stimulation would be similar either way. Proteins bound to FEN1 could be tethered to the flap base by the interaction of FEN1 with PCNA, potentially improving their availability when flaps become long. These findings also support a model in which cleavage by FEN1 alone is the preferred pathway, with the first opportunity to complete cleavage, and is stimulated by components of the backup pathway.